A potencialidade da fibra do bambu da espécie (Dendrocalamus giganteu) para uso em materiais compósitos cimentíceos - Araújo, João Carlos Leite de (Universidade Federal Rural do Semi-Árido, 2017)
The present work has the purpose of making a physical analysis of bamboo fiber, with the use of Wetting-Drying cycles for traction and absorption tests that allowed the characterization of the samples. The goal is to know if just one wetting-drying cycle is enough to reduce the absorption of bamboo fibers and if this treatment compromises fiber strength. Samples of bamboo were collected. The samples were taken from a property in the southern state of Ceará, Mauriti. The species of bamboo is Dendrocalamus giganteu and was between 3 and 5 years old. In the absorption test was obtained a reduction in Cyclized Fiber (CF) absorption of 6% in relation to Uncycled Fiber (UF). In the direct traction test on the rupture of 20 CF and UF test bodies, were obtained an average resistance to the traction tension of 11.24 MPa for UF and 8.96 MPa for CF. The treated fiber had a 25% reduction in its traction resistance compared to untreated fiber. It can be concluded that only one wetting-drying cycle was not able to significantly reduce the absorption power of the fibers, but is already enough to compromise the fiber resistance.
Keywords: Fibras vegetais; compósitos reforçados com fibras vegetais; fibra do bambu; ciclo de moagem e secagem; caracterização das fibras do bambu; plant fibers; reinforced composites with vegetable fibers; bamboo fiber; wetting-drying cycle; characterization of bamboo fibers; ENGENHARIAS::ENGENHARIA CIVIL